2021
DOI: 10.3390/ijms22116100
|View full text |Cite
|
Sign up to set email alerts
|

The Propensity of the Human Liver to Form Large Lipid Droplets Is Associated with PNPLA3 Polymorphism, Reduced INSIG1 and NPC1L1 Expression and Increased Fibrogenetic Capacity

Abstract: In nonalcoholic steatohepatitis animal models, an increased lipid droplet size in hepatocytes is associated with fibrogenesis. Hepatocytes with large droplet (Ld-MaS) or small droplet (Sd-MaS) macrovesicular steatosis may coexist in the human liver, but the factors associated with the predominance of one type over the other, including hepatic fibrogenic capacity, are unknown. In pre-ischemic liver biopsies from 225 consecutive liver transplant donors, we retrospectively counted hepatocytes with Ld-MaS and Sd-M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…In NAFLD, progression to NASH is characterized by increased LD size, hepatocyte hypertrophy and inflammation [ 2 , 5 ]. Surprisingly, the ROSI group exhibited a true microvesicular steatosis mixed with macrovesicular steatosis, while PEP2 and HFD groups appeared to have macrovesicular steatosis, which is considered more pathological [ 20 , 21 , 22 ]. However, PEP2 tended to decrease LD area compared to HFD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In NAFLD, progression to NASH is characterized by increased LD size, hepatocyte hypertrophy and inflammation [ 2 , 5 ]. Surprisingly, the ROSI group exhibited a true microvesicular steatosis mixed with macrovesicular steatosis, while PEP2 and HFD groups appeared to have macrovesicular steatosis, which is considered more pathological [ 20 , 21 , 22 ]. However, PEP2 tended to decrease LD area compared to HFD.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, PEP2 group presented a macrovesicular steatosis with small LD vs. macrovesicular steatosis with large LD in the HFD group. The importance of LD size is highlighted by findings showing that macrovesicular steatosis is linked to fibrosis and microcirculation impairment in rodents [ 31 , 32 ] and fibrogenesis in humans [ 20 ]. Moreover, the extent of macrovesicular steatosis can impact liver transplantation and graft survival in humans [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…But, the ZXBZ-L group had generally fewer large lipid droplets than the vehicle group ( Figure 2F ). Many previous studies demonstrated that the larger size of lipid droplets would make more serious hepatocyte injuries ( Ferri et al, 2021 ; Mashek, 2021 ). Therefore, we speculated that the low dosage of ZXBZ decoction could protect livers by reducing the formation of large hepatic lipid droplets and increasing the PGC-1α expression.…”
Section: Discussionmentioning
confidence: 99%
“…The hepatic lipid content and size of the lipid droplets were also larger in PNPLA3 148M risk allele carriers, which is in accordance with an earlier finding linking large lipid droplets to PNPLA3 148M carriers. [ 34 ] Recently, a small study in 26 patients with NAFLD, using another antibody, found that PNPLA3 was predominantly expressed in hepatic stellate cells and was elevated in PNPLA3 148M carriers. [ 35 ] Although the cellular localization of PNPLA3 in that study differs from both our study and from that in Donati et al, [ 33 ] it indicates that hepatic PNPLA3 levels may also be associated with liver fibrosis in patients with more advanced liver disease.…”
Section: Discussionmentioning
confidence: 99%